Climate Change and Cyclical Unemployment in Indonesia - Yunus, Amanus Khalifah Fil’ardy; Mubarak, Munawwarah S.; Yunus, Akbar Mandela Arumattulabala (International Journal of Economics and Financial Issues, 2024)
Cyclical unemployment can transform into a permanent scar in the long term. Meanwhile, climate change is known to be systemic and has a long-term impact. Therefore, this research will investigate the effect of climate change on cyclical unemployment and analyze the potential for hysteresis. In the first stage, we will estimate cyclical unemployment using the Philips curve concept. The data employed is secondary data from Statistics Indonesia, which is processed using the simultaneous equation method. The results show that warming temperatures do not affect cyclical unemployment directly. However, the decrease in economic growth caused by the warming temperature can increase cyclical unemployment. These results also indicate the occurrence of hysteresis in Indonesia.